The Relationship between Nurse Work Discipline and Quality of Service to Patients at the Long Pahangai Community Health Center Outpatient Clinic in 2023 - Maria Sofia Hong; Rasmun; Abd Kadir (Formosa Journal of Science and Technology, 2023)
In this study the type of quantitative researcher with analytical studies and with cross sectional design. In this study, researchers wanted to know the relationship between nurses' work discipline and the quality of service to patients at the outpatient poly of Long Pahangai Health Center in 2023. Accidental Sampling is a sampling technique based on chance, so that researchers can take samples from anyone they meet without prior planning. The results of the Chi Square statistical test of the SPSS 25 program in table 4.4 obtained a P-value value of < α where the P-value (0.000) < α (0.05) so that it can be concluded that there is a significant relationship between work discipline and service quality at the Long Pahangai Health Center Outpatient Poly, Mahakam Ulu Regency in 2023. The results of the Chi Square statistical test of the SPSS 25 program in table 4.4 obtained a P-value value of < α where the P-value (0.000) < α (0.05) so that it can be concluded that there is a significant relationship between work discipline and service quality at the Long Pahangai Health Center Outpatient Poly, Mahakam Ulu Regency in 2023.